A Note on Hedging a Loan Portfolio - Peter Welzel; Udo Broll (Universität Augsburg, Institut für Volkswirtschaftslehre, 2003)
In the framework of the industrial economics approach to banking we extend the analysis of hedging against default on loans to the case of two types of credit risk. Standard results on the optimal hedge volume and the hedging effectivity from the single?risk case are shown to carry over to the portfolio case in a non?trivial but intuitive way. – – In the framework of the industrial economics approach to banking we extend the analysis of hedging against default on loans to the case of two types of credit risk. Standard results on the optimal hedge volume and the hedging effectivity from the single-risk case are shown to carry over to the portfolio case in a non-trivial but intuitive way.
urn:nbn:de:bvb:384-opus4-712075
Keywords: G21; 330; banking; credit risk; loan portfolio; credit derivative; hedging; Kreditrisiko; Hedging; Portfolio-Management; Theorie